Ferimentos faciais: relato de caso - Gaetti-Jardim, Ellen Cristina [UNESP] (2010)
Facial injuries vary in their clinical characteristics and complexity, deserves an appropriate approach for each case, considering that the failures may result in aesthetic and functional changes that can be harmful both functionally and psychologically. Aspects such as exposure time of the injury, anesthesia, suture materials and tetanus prophylaxis are important factors. The objective is to present a case of extensive facial injuries in an automobile accident patient.